The Role of Household Women (IRT) With a Traditional Shop a Livelihood in Fulfillment of Family Needs in Serijabo Village - Azizah Husin; Liza Ayu Pebrianti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The role of homemakers in irt brackets whose livelihood is traditional stalls in meeting family needs in Serijabo village aims to find out how essential homemakers are in helping their family's economy with indicators of family income, fulfilling family health, fulfilling education needs and fulfilling family food. This study uses a qualitative approach with a descriptive method. This research is located in hamlet 1 RT 002 RW 000 Serijabo Village. The research subjects amounted to 4 people because there are families whose income comes from traditional stalls. For data collection techniques in this study, the authors use observation and interviews. The data analysis technique used is the howling theory, namely collecting data, reducing data, presenting data and drawing conclusions. The results of the study indicate that family income is sufficient, measured by the income generated by each family, and the fulfilment of health for all health is sufficient, measured in terms of their diet and environmental cleanliness. . Fulfilling children's educational needs is almost all good, but there is one family whose children fail to go to school, only elementary school graduates, there are several factors that influence it, such as economic factors, family factors and others. Fulfilment of all family food can be seen in their daily diet and the health of their environment.